Интегральное уравнение первого рода с логарифмическим ядром, заданное на системе интервалов - Полянская, Татьяна Семеновна (НТУ "ХПИ", 2017)
Рассмотрено интегральное уравнение первого рода с логарифмическим ядром, к которому приводит ряд задач дифракции волн. Это уравнение сведено к системе интегральных уравнений на отрезке. Проведена дискретизация этой системы на основе метода дискретных особенностей. Введены пары гильбертовых пространств и операторы в них, соответствующие заданной и дискретной задачам. С их помощью доказана однозначная разрешимость дискретной задачи и дано строгое обоснование оценки скорости сходимости решения дискретной задачи к точному решению интегрального уравнения.

We consider an integral equation of the first kind with a logarithmic kernel, which arises in a number of problems of wave diffraction. This equation is reduced to a system of integral equations on a segment. Discretization of this system is carried out on the basis of the method of discrete singularities. A pair of Hilbert spaces and operators in them corresponding to predetermined and discrete problems is introduced. With their help, we prove the unique solvability of the discrete problem and give a rigorous justification of the rate of convergence of the solution of the discrete problem to the exact solution of the integral equation.
Integral equations of the first kind with logarithmic kernel given on a system of intervals
Keywords: математическая физика; метод дискретных особенностей; логарифмические особенности; дифракция волн; integral equations; logarithmic kernel; method of discrete singularities